RESEARCH ON CALCULATION METHOD OF AXIAL COMPRESSION LOAD-CARRYING CAPACITY OF INTEGRALLY STIFFENED PANEL - LIU Cun; WAN YaFeng; LI Jian (Jixie qiangdu)
The accurate calculation of load-carrying capacity of integrally stiffened panels under axial compression is the key factor for designing and analyzing of wing panel,which is essential for the aircraft wing structural efficiency and weight control,it is necessary to study a method that can calculate the load-carrying capacity of integrally stiffened panels under axial compression accurately. This paper proposes the equivalent calculating method based on the bending resistance of stiffened panels,axial compression tests of stiffened panels have verified the accuracy of the calculation method for the three types skin effective width,influences of shot peening on compressive strength of wing stiffened panel are considered by comparison on crippling test results of shot peened and unpeened panel element,afterwards,a more perfect and accurate,practical engineering calculation method is established.